Criteria and methodology for intervention in vernacular architecture and earthen heritage - Correia, Mariana (2022)
The assessment of criteria and methodology for intervention definition, its significance and the fact that there is a tendency for a non-rigorous application of the terms contributes for its inaccuracy in the field, having therefore a relevant negative impact on the decision-making process, regarding heritage intervention. This paper addresses the concepts associated with criteria and methodology for intervention in vernacular architecture and earthen heritage. A specific literature review is entailed for criteria and methodology for intervention; their frameworks are established; and key-criteria for intervention; and methodology key-components to consider for intervention are addressed. This assessment aims to contribute for a further well-defined and clear ground of work in conservation practice, leading to a more coherent and consistent intervention in heritage.